Enhancing Digital Literacy Among Indigenous Senior Citizens: A Necessity for Inclusive Empowerment (Khwopa Journal, 2026)
The study aims to explore the digital literacy situation, practices, and challenges faced by the older people of age 60 and above in Bhaktapur District, Nepal, which is a culturally important indigenous community with a relatively small contact with digital infrastructure. Taking the context of increasing discussion related to social inclusion and technological participation in the low-resource countries of Global South Asia, the study addresses an important empirical gap, namely how much senior citizens in the low-resource countries of Global South Asia can embrace and successfully utilize digital technologies.The methodology for this study was interpretive qualitative in which 11 purposive sample senior citizens, six male and five female were interviewed semi-structured from the indigenous Newar community of Bhaktapur. Seven with formal education and four illiterate participants were the informants. To gain insight into participant's experiences that were "lived out" in the digital domain, a thematic analysis approach was used, following the inductive coding paradigm of Braun and Clarke (2006). The study revealed 7 key themes: intergenerational digital support; cultural and linguistic barriers; digital exclusion/social isolation; self-directed motivation and adaptive learning strategies; perceived benefits/risk of digital use; infrastructural/device access constraints. To the contrary, there were a few participants who didn't have any formal education who showed to be functional with QR codes, mobile banking, and ATM interfaces; while some educated retirees showed anxiety around technology. The main structural barriers to digital adoption were the limitations on the bilingual interface, poor network connectivity and high device expenses. Despite being more exposed to digital worlds, senior citizens in Bhaktapur still cannot fully participate due to systemic barriers. The results highlight the need for digital literacy interventions especially for the elderly indigenous population of Nepal, culturally and linguistically relevant content design, community based support and mechanisms, and policy mechanisms suitable for the age population to improve meaningful digital inclusion.